The Conflicts Between Female Inmates' Needs And Prisoners' Goals - Mohr, Aline L. (1976)
A comparison of the purposes behind the existence of male and female institutions reveals that several common goals exist: custody, deterrence, and rehabilitation. An examination of these goals of women's prisons can be best understood in the context of whom they are aimed to serve. If the goals are to serve society alone, then the custody of female offenders is undoubtedly viewed as an accomplished goal, since society is protected and secure from the infliction of criminal acts by these female offenders. However, if the goals are directed at the inmates as well, deterrence of further criminal activity and rehabilitation have failed both the society and the inmates as workable goals. Women sentenced to prison frequently return; in fact, it has been estimated that anywhere from fifty to eighty-five percent are recidivists. Furthermore, the women are generally not rehabilitated. Upon release, they are ill-prepared to cope with life on the outside. One former inmate stated, You just come out BAMB. And you don't know how to deal with it. You don't have a family to go to half the time. You don't have a home or job. . . . A lot of times the only thing left for a person to do is commit new crime. If one agrees with Herbert Packer that the goal of rehabilitation is justified by the desire to reform the offender so further criminal activity will cease, and that each offender must be treated individually according to her needs then one must ask, why are not female offenders rehabilitated? This study attempts to develop an answer to this question by first researching the crimes committed by female offenders. The crimes committed reveal problems of which the prisons fail to take account. This leads to an inevitable conflict of prison goals with inmate needs. This conflict raises two alternatives: (1) one can work from the assumption that prisons will long continue in existence, so that any attempt to bring goals and needs closer together will have to be developed by working with the prison system, or (2) one can work from the assumption that alternatives to prison, as it is now known, must be found in order to effectuate the goals of prison and society and yet accommodate the needs of the female offenders